Synergic Influence of River Gravels and Crushed Aggregates on the Mechanical Properties of Concrete - Arif Usman; Muhammad Haris Javed; Farhan Abbas; Faraz Ali Channa; Sami Ullah (Journal of ICT, Design, Engineering and Technological Science, 2023)
The study aims to replace crushed aggregate with river gravel and analyze the results of both the concrete, and compare them with each other. From the comparison, it was found that the workability of concrete was high about 19% when river gravel was used in concrete and was low when crushed aggregate was used in concrete. On the other side, the combination of both Quarry and river gravel was found to be 36% less workable than river gravel. This was because of the crushed used with river gravel crush aggregate has a greater surface and diamond cut. Comparing the Compressive strength of Quarry, gravel, and the combination of both it was observed that on average Quarry and Gravel combination concrete was 20 % stronger than concrete with quarry crushed used as aggregate and 10 % stronger than river gravel. The river gravel can be used as aggregate in concrete in a lighter structure or foundation to provide a hard and level surface.